The inflammasome adaptor ASC contributes to multiple innate immune processes in the resolution of otitis media. Issue 2 (February 2015) - Kurabi, Arwa; Lee, Jasmine; Wong, Chelsea; Pak, Kwang; Hoffman, Hal M; Ryan, Allen F; Wasserman, Stephen I
This study was designed to understand the contribution of the inflammasome and IL-1β activation in otitis media (OM). We examined the middle ear (ME) response to non-typeable Haemophilus influenzae (NTHi) in wild type (WT) mice using gene microarrays and a murine model of acute OM. Expression of members of the NOD domain-like receptor family of inflammasome genes was significantly up-regulated early in NTHi infection of the ME, potentially activating specific downstream regulatory cascades that contribute to the proliferative inflammatory response observed during OM. Expression of the pro-forms of the inflammasome targets IL-1β and IL-18 were also up-regulated. To evaluate the role of inflammasome-mediated cytokine maturation, NTHi-induced OM was examined in Asc −/− -deficient mice and compared with that seen in WT mice. Mice lacking the Asc gene showed near absence of IL-1β maturation in the ME and a reduction in leukocyte recruitment and infiltration to the cavity, and their macrophages exhibited reduced phagocytosis of NTHi. These inflammatory defects were linked to an increase in the degree and duration of mucosal epithelial hyperplasia in the ME of Asc −/− mice, as well as a delay in bacterial clearance from their MEs. These data demonstrate an important role for the inflammasome and cytokine processing in the course and resolution of OM.